Earthquake-Induced Ground Deformation Assessment via Sentinel-1 Radar Aided at Darbandikhan Town. (7th June 2022) - Saed, Farman Galeb; Noori, Abbas Mohammed; Kalantar, Bahareh; Qader, Waleed Mohammed; Ueda, Naonori
Abstract : Deformation monitoring has conventional increasing consideration in recent years due to its great importance in modern engineering. Darbandikhan town was hit by a strong earthquake on 12 th November 2017 which is the Sarpol-e Zahab earthquake. Interferometric Synthetic Aperture Radar (InSAR) technique has been used to investigate Darbandikhan town stability and the surrounding areas of the Kurdistan region in Iraq. The purpose of this research is to estimate the ground vertical displacement induced by the earthquake as well as the east-west deformation components. Moreover, previous research covered more of Iran's side country that the earthquake had an impact on with little on Iraq's side (Northern-eastern of Iraq), so it was worth researching on Darbandikhan town and surrounding structures to estimate the displacement on its infrastructures. For this study, two pairs of Sentinel-1 Synthetic Aperture Radar (SAR) images are used from each ascending and descending tracks over the study area to validate the work. Then, two differential interferograms are created from these images, along Darbandikhan town and the surrounding areas. These differential interferograms are then converted to line of sight (LOS) displacements using open source software (SNAP 8.0). The overall vertical displacement of the residential area of Darbandikhan was estimated from -4 to -10 cm after the earthquake, and the overall east-west displacement was ranging from 2 to 6.4 cm. The current study does not only examine the northern east of Iraq but the whole area of Iran and Iraq in general that lies within the influence of the earthquake. This research could be useful to estimate the overall deformation of Darbandikhan town in particular and the whole area in general. Therefore, the authorities and civil engineers could think of more sustainable buildings and structures before they start to plan within the area of earthquake impact.